A Feeling of Ambiguity: A Qualitative Content Analysis of Managers’ Experiences of Evidence-Based Practice in Swedish Primary Care - Abelsson T; Karlsson AK; Morténius H (Dove Medical Press, 2022)
Tobias Abelsson,1,2 Ann-Kristin Karlsson,1 Helena Morténius1,3 1Department of Public Health and Community Medicine, University of Gothenburg, Gothenburg, Sweden; 2Department of Research and Development, Region Halland, Halmstad, Sweden; 3Department of Child and Adolescent Mental Health, Region Halland, Halmstad, SwedenCorrespondence: Tobias Abelsson, Email Tobias.Abelsson@regionhalland.seBackground: The Primary care manager plays a vital role in promoting a research culture in the healthcare center. The position involves both the implementation of organizational directives and patient care. The research culture and use of evidence influence each individual healthcare professional and ultimately the quality of patient care.Purpose: To describe primary healthcare managers' understanding of evidence-based practice in the Swedish primary healthcare context and their ability to influence its implementation.Methodology: Qualitative content analysis of data collected in individual interviews.Results: In general, managers expressed a positive view toward the use of evidence in daily practice. However, they were sometimes hesitant about fully implementing evidence-based results. This was mostly attributed to the struggle of balancing finances and allocating sufficient time for staff to keep up with and engage in evidence-based practice.Conclusion: The organizational culture impacts the mind-set of all co-workers including managers. Those managers influenced by traditions and norms may fall into the trap of devaluing the benefit of research and evidence. The inherent feeling of being alone and without guidance in some matters related to evidence-based practice inevitably leads to inconsistency and ambiguity. The use of clinical pathways that constitute one form of evidence has become a substitute for proper, careful, individual investigation, implementation, and evaluation of each patient case. This means that managers experience moral and physical stress when trying to meet organizational, staff, and patient demands.Practice Implication: Awareness of managers' influence and experience of working according to evidence-based practice is valuable to gain an insight into how Swedish primary healthcare functions at local level. Illuminating and discussing evidence-based practice is an assurance of quality that contributes to many aspects of the overall safety of care.Keywords: information dissemination, management, primary healthcare, EBP, evidence-based practice